Capacity and Energy Local Flexibility Markets for Imbalance and Congestion Management - Paredes-Parrilla, Ángel; Aguado-Sánchez, José Antonio (IEEE, 2021)
Local Flexibility Markets (LFMs) are a type of marketplace where flexibility products are traded to solve network issues. In the last several years, efforts were made in the field of LFM for imbalance and congestion management, but they only trade with energy products with highly complex mathematical descriptions. This paper presents a description of an efficient LFM formulation where both capacity and energy products are considered through a linear programming (LP) optimization problem to clear the LFM in a centralized manner. It is assumed that flexibility assets present in the distribution network are managed by Aggregators (Aggs). Results from this centralized approach are provided under three different scenarios, demonstrating the feasibility of the proposed approach to solve network issues at a distribution level
Keywords: Industria -- Producción; Local Flexibility Market; Energy Products; Capacity Products; Congestion; Imbalance